Intergrasi Karakter Religius Pada Mata Pelajaran UAN - Ida Rahmawati; Syafik Ubaidilla (Universitas Islam Tribakti Lirboyo Kediri, 2022)
This paper aims to take a deeper look at how to inculcate religious character in subjects that must have a national final examination at Madrasah Ibtidaiyah. This study uses a qualitative method with a descriptive approach. Key informants are school principals, curriculum representatives, subject teachers, and religious teachers. The results of this study indicate that the inclusion of character education values ​​has appeared in the syllabus and lesson plans, often called the syllabus and character lesson plans in which the expected religious character values ​​appear. This activity started from the concept of routine activities at school, which are always directly related to religious values. This integration can also be seen in the RPP for sports subjects.